2020
DOI: 10.1177/1756284820927550
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medications in the management of inflammatory bowel disease

Abstract: The use of complementary and alternative medications (CAM), products, and therapies not considered to be part of conventional medicine is common among patients with inflammatory bowel disease (IBD). Patients often turn to these therapies as they are considered natural and safe, with significant benefit reported beyond disease control. There is emerging evidence that some of these therapies may have anti-inflammatory activity; however, robust evidence for their efficacy in modulating disease activity is current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 96 publications
(142 reference statements)
0
16
0
Order By: Relevance
“…care[4]. In this first ever detailed assessment of CAM use in AIH patients, we observed that over half (56%) of all participants reported ever using CAM, and 42% had used CAM after AIH diagnosis.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…care[4]. In this first ever detailed assessment of CAM use in AIH patients, we observed that over half (56%) of all participants reported ever using CAM, and 42% had used CAM after AIH diagnosis.…”
mentioning
confidence: 81%
“…Multiple therapeutic options are available for liver-specific inflammation observed in patients AIH, yet patients continue to suffer from poorly-controlled extrahepatic symptoms (i.e., fatigue, insomnia, anxiety, depression, and pain) [14]. We previously observed that 25% of AIH patients have used cannabidiol (CBD) to treat these symptoms [4], yet utilization of CAM outside CBD is unknown. We aimed to examine the overall use of CAM strategies among AIH patients using a large, well-established online cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of UC mainly includes medical management and colectomy, but current therapies are limited because a large proportion of patients with UC are resistant or intolerant to standard drug treatments [ 5 , 6 ]. Since dissatisfaction with conventional medication, complementary and alternative therapies, including traditional Chinese medicine (TCM), dietary supplements, probiotics, and mind/body interventions [ 7 , 8 ], are commonly used in patients with UC [ 9 , 10 ]. Among them, the therapeutic efficacy and safety of several TCM formulas in IBD have been shown in some double-blind randomized controlled trials [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence and patterns of CM use are well characterised in various chronic conditions, including cancer (Wong et al, 2020), cardiovascular disease (Than et al, 2019), diabetes (Raja et al, 2019), and inflammatory bowel disease (Picardo et al, 2020). High levels of CM use are reported by older people to manage such chronic conditions (Smith et al, 2019).…”
Section: Introductionmentioning
confidence: 99%